Pengaruh Brand Image, Brand Awareness dan Brand Trust Terhadap Customer Loyalty pada Dee Coffee House Sidoarjo - Pratama, Duta Akbar; Rusdianto, R. Yuniardi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to determine the effect of brand image, brand awareness and brand trust on customer loyalty at Dee Coffee House. The method used in this research is quantitative type method. The population in this study were Dee Coffee House customers. The sample used was 100 respondents taken using purposive sampling technique. Obtained F count of 20.745 and a significance value of 0.000 <0.05, then the F test results show that the variables Brand Image (X1), Brand Awareness (X2), and Brand Trust (X3) simultaneously affect Customer Loyalty (Y). In the brand image variable, the T value is obtained 3.405> t table 1.984, then H0 is rejected and H1 is accepted, meaning that the Brand Image variable partially affects Customer Loyalty. In the brand awareness variable, the T value is 2.722> t table 1.984, then H0 is rejected and H2 is accepted, meaning that the Brand Awareness variable partially affects Customer Loyalty. In the Brand Trust variable, the T value is 5.687> t table 1.984, then H0 is rejected and H3 is accepted, meaning that the Brand Trust variable partially affects Customer Loyalty.